ECOLOGICAL TEACHER TRAINING AND ESSENCE ENVIRONMENTAL EDUCATION (Pedagogy of Higher and Secondary Education, 2008)
The article tells about ecological teacher training and about the essence of ecological education; actual tasks of ecological teacher training to realization o f tasks of ecological education; analysis of modern methodical approaches to ecological teacher training.